1998
DOI: 10.1007/bf01320895
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in protein methylation: Enzymatic methylation of nucleic acid binding proteins

Abstract: Heterogeneous nuclear RNP protein A1, one of the major proteins in hnRNP particle (precursor for mRNA), is known to be posttranslationally arginine-methylated in vivo on residues 193, 205, 217 and 224 within the RGG box, the motif postulated to be an RNA binding domain. Possible effect of NG-arginine methyl-modification in the interaction of protein A1 to nucleic acid was investigated. The recombinant hnRNP protein A1 was in vitro methylated by the purified nuclear protein/histone-specific protein methylase I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…They are catalyzed by protein methylases (11)(12)(13)(14) that specifically recognize the amino acid sequences up-and downstream of the amino acid to be methylated. Since the sequences up-and downstream of the four methylated amino acids in the ␣-subunit of methyl-coenzyme M reductase are very different (2), it has to be concluded that in the post-translational modification four different SAM-dependent protein methylases are involved.…”
Section: Discussionmentioning
confidence: 99%
“…They are catalyzed by protein methylases (11)(12)(13)(14) that specifically recognize the amino acid sequences up-and downstream of the amino acid to be methylated. Since the sequences up-and downstream of the four methylated amino acids in the ␣-subunit of methyl-coenzyme M reductase are very different (2), it has to be concluded that in the post-translational modification four different SAM-dependent protein methylases are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Protein arginine methylation commonly occurs in arginine-glycine-rich (RG-rich) domains of RNA-binding proteins (Aoki et al, 2002;Christensen and Fuxa, 1988;Cote et al, 2003;Kim et al, 1998;Mears and Rice, 1996;Pelletier et al, 2001;Rho et al, 2001). An eight-member family known as the protein arginine methyltransferases (PRMTs) mediates this post-translational modification.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine methylation of nonhistone proteins has been known for nearly four decades, regulating various cellular processes such as transcription and RNA processing, and DNA replication and repair (1,2). However, histone arginine methylation and its role in gene regulation were discovered much more recently (3).…”
mentioning
confidence: 99%